Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
The nth term will be:
- [tex]a_{93}=-925[/tex]
Step-by-step explanation:
Given the sequence
-5, -15, -25, ...
An arithmetic sequence has a constant difference 'd' and is defined by
[tex]a_n=a_1+\left(n-1\right)d[/tex]
computing the differences of all the adjacent terms
[tex]-15-\left(-5\right)=-10,\:\quad \:-25-\left(-15\right)=-10[/tex]
The difference between all the adjacent terms is the same and equal to
[tex]d=-10[/tex]
The first element of the sequence is:
[tex]a_1=-5[/tex]
Thus, the nth term will be:
[tex]a_n=a_1+\left(n-1\right)d[/tex]
substituting the values [tex]d=-10[/tex]; [tex]a_1=-5[/tex]
[tex]a_n=-10\left(n-1\right)-5[/tex]
[tex]a_n=-10n+5[/tex]
Plug in n = 93 to determine the nth term
[tex]a_{93}=-10\left(93\right)+5[/tex]
[tex]a_{93}=-930+5[/tex]
[tex]a_{93}=-925[/tex]
Therefore, the nth term will be:
- [tex]a_{93}=-925[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.